2021
DOI: 10.1155/2021/5534227
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Cartilaginous Endplate Degeneration Based on Magnetic Resonance Imaging

Abstract: In order to carry out the evaluation of cartilaginous endplate degeneration based on magnetic resonance imaging (MRI), this paper retrospectively analyzed the MRI data from 120 cases of patients who were diagnosed as lumbar intervertebral disc degeneration and underwent MRI examinations in the designated hospital of this study from June 2018 to June 2020. All cases underwent conventional sagittal and transverse T1WI and T2WI scans, and some cases were added with sagittal fat-suppression T2WI scans; then, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As per the study conducted earlier [21], the CEP undergoes natural, stress and damageinduced degeneration which has a heavy negative influence on weight bearing and its biochemical metabolism. The authors [34] opined that the Ca2+ content was found to be significantly higher in the CEP tissues that recorded disc degeneration.…”
Section: Ivdd -Overview and Diagnosis And Treatment Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…As per the study conducted earlier [21], the CEP undergoes natural, stress and damageinduced degeneration which has a heavy negative influence on weight bearing and its biochemical metabolism. The authors [34] opined that the Ca2+ content was found to be significantly higher in the CEP tissues that recorded disc degeneration.…”
Section: Ivdd -Overview and Diagnosis And Treatment Methodsmentioning
confidence: 88%
“…As mentioned earlier, cytokines are accountable for activation as well as regulation of these MMPs and ADAMTS and also its subsequent effects [32]. With increasing age [21], the vertebral endplate blood vessels get reduced whereas the CEP gets ossified and undergoes local calcification, as a result of injury, inflammation. However, changes in the mechanical environment does not induce calcification in the CEP [33].…”
Section: Ivdd -Overview and Diagnosis And Treatment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%